Seizing Public Digital Dominance (The Phenomenon Of Mainstream Islamic Media Digital Battle) - Hamidah, Kamilia (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
The authority of digital public discourse indirectly impacts one's religious point of view, the phenomenon of digital religion has caused mainstream Islamic websites to strive for the dominance of the public digital mass. This paper will examine the phenomenon of competition among mainstream Islamic websites and mainstream non-affiliated websites in seizing public digital dominance. Data Reportal on Digital Indonesia 2023 put Indonesia as the largest internet users in the world, with a population of around 277,7 million with a total active internet user of 212,9 million, internet penetration stood at 77,0 percent. Indonesia also home to 167,0 million social media users equating to 60,4 percent of the total population. Total of 352,8 million cellular mobile connections were active in Indonesia, this figure equivalent to 128,0 percent of the total population. The paper elaborates the prevalent competition between Islamic media using a phenomenological approach based on digital data and a variety of digital analysis tools. This study demonstrates how the intensity of contestation persists and has subsequently created digital communities with divergent religious viewpoints that have subconsciously created social segmentation that strengthens group exclusivism.